The influence of gender and age on the prevalence of periodontal pockets (Pesquisa Odontológica Brasileira, 2000)
The aim of this study was to evaluate the influence of risk factors on the prevalence of periodontal pockets in patients attending the clinic of the School of Dentistry of Piracicaba - Unicamp. The sample consisted of 100 patients attended by the students from the third and fourth years of undergraduation. The data were taken from anamneses and clinical - periodontal records. Probing depths were considered to be 3, 5, 7 and 10 mm, according to the WS diagnosis system (SALLUM, 1996). The results were compared regarding pockets depths and the risk factors age and gender. Also, the distribution of pockets among the sextants was observed. This study indicated a major prevalence of periodontal pockets in men and an increase in probing depth in patients older than 31 years. The distribution of pockets among the sextants was relatively uniform in all studied groups.